Sinus rhythm variability in myocardial infarction patients during long-term out-patient rehabilitation, including physical training - G. G. Efremushkin; A. A. Efremushkina; A. G. Akimochkina (Российский кардиологический журнал)
Heart rate variability was measured by cardiointervalography in 49 individuals with acute myocardial infarction (MI), during systematic physical training as a component of the out-patient rehabilitation program. Follow-up period lasted for one year. In the main group (n = 25), controlled physical training sessions, with workload of 50- 60 % from baseline level, took place twice a week. In the control group (n = 24), rehabilitation program included dosed walking, with individually calculated pace velocity. Participants were examined at baseline, 3, 6, and 12 months later. Chronic physical training decreased sympathic tonus and stabilized parasympathic tonus, normalized the work of body regulatory mechanisms. Moreover, physical training stabilized autonomic tonus and reactivity, due to declined sympathicotony. Absence of physical training resulted in significantly reduced number of patients with normal autonomic reactivity.